Cross Axis Wind Turbine® - Chong, W.T.; Kong, Y.Y. (University of Malaya, 2015)
A cross axis wind turbine is disclosed, which comprises of cross axis arrangement. The wind turbine consists of three vertical blades and six horizontal blades arranged in cross axis orientation. The six horizontal blades serve as the radial arms that link the three vertical blades and the hubs through connectors to form the cross axis wind turbine (CAWT). Three horizontal axis blades that make up as the upper radial arm connects the top part of the vertical blades to the hub through the top connectors. The other three horizontal axis blades that make up as the lower radial arm connects the bottom part of the vertical axis blades to the hub through the bottom connectors. To avoid air flow blockage or interference between the top radial arm and the bottom radial arm, the horizontal axis blade radial arm at the top part of the turbine is offset at an angle of 30Â° with respect to the bottom radial arm. In the present invention, the air stream can be channeled from the bottom of the turbine through the bottom radial arm, and the air streams that did not interact with the bottom radial arm will eventually interact with the top radial arm. The air streams channeled from the bottom of the wind turbine and moving upwards will interact with the horizontal blades and this will eventually improve the self-starting capability of the CAWT. This trademark registered in class 7.